Sharing Screen Capture Android Application - Uttaram, I G.; Mahendra Darmawiguna, I Gede; Gede Sunarya, I Made (Universitas Pendidikan Ganesha, 2013)
Currently education and technology are something that is very closely related. Education would become more interesting through technology. Class activities in the learning process become more interactive by using projector in presentation. Therefore, the teacher easily teaches the knowledges to the students because they use more imaginative audio and visual media. At this time, mobile devices has become a primary needs. The children, teenagers, and adults use it very well, such as notebooks, smartphones, and tablet pc. Especially with the spread of the android os as public resources, thus making the penetration of mobile devices such as smartphones and tablet pc are becoming increasingly vociferous. Even the mobile world has created a new mobile device that term